Law No. 141 of the year 2021 Amending Certain Provisions of the Penal Code Promulgating by Law No. 58 of the Year 1937 = قانون رقم 141 لسنة 2021 بتعديل بعض أحكام قانون العقوبات الصادر بالقانون رقم 58 لسنة 1937 - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic